Factors affecting the diffusion of meloxicam from different bases - Abdul-Rassol A. Alaa; Mariee K. Nidhal; Mehsin B. Masar (College of Pharmacy / Mustansiriyah University, 2005)
The value of meloxicam as a non-steroidal anti-inflammatory drug is well established. This study was carried out to formulate a stable and effective meloxicam topical preparation. The in vitro release of meloxicam from different semisolid bases, which are: o/w, w/o emulsions, sodium carboxy methylcellulose gel and carbomer gel base was established. The study also involved the diffusion of meloxicam through excised mouse skin with different concentrations using carbomer gel in addition to the effect of different enhancing agents such as PG (Propylene Glycol), methyl salicylate, urea, oleic acid, DMSO (Dimethyl Sulfoxide), xanthan gum and PEG1000 (Poly Ethylene Glycol) and the last one gave the highest diffusion. The results showed that the selected formula of meloxicam was not irritant and this result was supported by histological examination. In addition, the results showed that the use of disodium EDTA (stabilizer) gave more stable formula where the expiration date was 2 years compared to 0.8 year when using both dl- α tocopherol and blank formula. The results showed that the temperature and the storage period led to decrease both the diffusion rate and viscosity of meloxicam 1% gel but with little change in pH. On the other hand preliminary clinical study was carried out for 26 patients and the results indicated that 84.6% of patients got positive responses.